Neural Mechanisms of Dorsal and Ventral Visual Regions during Text Reading - Zhou, Wei; Wang, Xiaojuan; Xia, Zhichao; Bi, Yanchao; Li, Ping; Shu, Hua (Frontiers in Psychology, 2016)
When reading a narrative text, both the dorsal and ventral visual systems areactivated. To illustrate the patterns of interactions between the dorsal and ventral visual systems in text reading, we conducted analyses of functional connectivity (FC) and effective connectivity (EC) in a left-hemispheric network for reading-driven fMRI and resting-state fMRI (rs-fMRI) data. In reading-driven fMRI (Experiment 1), we found significant FCs among the left middle frontal gyrus (MFG), the left intraparietal sulcus (IPS), and the visual word form area (VWFA), and there were top-down effects from the left MFG to the left IPS, from the left MFG to the VWFA, and from the left IPS to the VWFA. In rs-fMRI (Experiment 2), we identified FCs and ECs for MFG-IPS and IPS-VWFA connections. In addition, the brain-behavior relationship in resting states showed that the dorsal connection was more associated with reading fluency relative to lexical decision. The combination of two experiments revealed that the MFG-IPS and the VWFA-IPS connections were shared connections both in reading-driven fMRI and rs-fMRI, and that the MFG-VWFA was specific connectivity in reading-driven fMRI. These results suggest that top-down effects from the dorsal visual system to ventral visual system play an important role in text reading.